Geographical mobility among retired US migrants living in the Northwestern region of Mexico bordering California, US - Lardiés-Bosque, Raúl (Bulletin of Geography. Socio-economic Series, 2016)
Mexico has become a regular destination for retirees coming from the USA. To date certain aspects of this group of migrants have been analysed, but little is known about those who have changed their place of residence to the Mexico- US border. In this article, the geographical mobility among retired US migrants living in the coastal area of northern Baja California, Mexico, is analysed. Firstly, reasons for retirees moving from the USA to this area are considered, and secondly, the contacts and relationships maintained with the country of origin, measured by the mobility which takes place between both countries; attention will be given to the reasons for these frequent trips, their periodicity, the means of transport used and the impacts. The main source of analysis will be 29 in-depth interviews conducted in 2009 with pensioners living in coastal municipalities of this northern area of Mexico.